Measurement of volatile organic compounds from indoor cannabis smoking and vaping: Direct effects and secondary transport - Amirashkan Askari; Xing Wang; Rachel Ortiz; Patricia Di Ciano; Ahmed N. Hassan; Sergio Rueda; Chung-Wai Chow; Arthur W.H. Chan (Elsevier, 2024)
Cannabis smoking and vaping are emerging sources of indoor air pollutants, given the current trends of decriminalization and legalization across different jurisdictions. Secondhand exposure at the drug consumption site and thirdhand effects through the potential transfer of cannabis emissions to a secondary area, are of public health significance. Here, we present data from an exploratory observational study that examined emissions from cannabis smoking and vaping within a realistic indoor environment by analyzing the gas-phase composition of the indoor air. Additionally, we explored the transfer of emissions to another indoor space as individuals departed from the initial drug consumption site. We observed no significant (p-value < 0.1) difference across smoking and vaping samples regarding total primary and transferred effects. Primary emissions of light aromatics and some sesquiterpenoids from cannabis smoking led to median indoor concentration enhancements 1.5 to more than 3 times higher than cannabis vaping. On the other hand, vaping primary indoor concentration enhancements were comparable to or higher than smoking values up to a factor of 4 among monoterpenoids. Sesquiterpenoids and some monoterpenoids showed median non-zero concentration enhancements in the secondary indoor space, underscoring the importance of cannabis emissions' thirdhand transport effects. The thirdhand transport was more efficient for semivolatile species, which have a higher affinity to consumers' body and clothing. We observed a positive and significant correlation between cannabis cigarette weight change during smoking and cannabinoids enhancement in the secondary space. Vapers' puff number was significantly and positively correlated with light aromatics enhancement in the secondary space. The correlation between the time spent within the primary smoking/vaping site and cannabinoids transport was significantly negative. These insights can facilitate the design and implementation of future projects to illustrate further cannabis smoking/vaping impacts on indoor air quality.